Left ventricular pseudoaneurysm - a rare complication of myocardial infarction - a systematic review - Adamowska, Agnieszka; Śniatała, Alicja; Bartkowiak, Hanna; Grubski, Damian; Ziarnik, Kacper; Nadolny, Filip; Jabłoński, Jędrzej; Kania, Martyna (Journal of Education, Health and Sport, 2024)
Introduction Left ventricular (LV) pseudoaneurysm is a rare but life-threatening complication following myocardial infarction (MI). Unlike true aneurysms, pseudoaneurysms lack myocardial elements in their structure, which increases the risk of rupture and sudden death. The diagnosis is challenging due to its often subtle and nonspecific symptoms. The high mortality rate associated with untreated pseudoaneurysms highlights the importance of awareness and prompt diagnosis. All patients after MI should receive specialized care and follow-up examinations to prevent unattended states of emergency. Purpose of research This systematic review aims to discuss a rare complication of MI in a form of LV pseudoaneurysm. Due to its potential asymptomatic course, it is important to highlight the importance of a meticulous clinical and echocardiographic follow-up in all patients with a history of MI. Materials and methods The study was conducted through search across PubMed and Google Scholar databases, using keywords such as “left ventricular pseudoaneurysm”, “myocardial infarction”, “post-infarction imagining”, “surgical treatment of pseudoaneurysms”. The analysis focused on scientific literature with validated insights into the pathophysiology, clinical presentation, diagnostic methods and treatment strategies of the MI complication in a form of left ventricular pseudoaneurysm. Results and conclusions The potentially fatal consequences of pseudoaneurysm dictate proactive approach in the treatment of patients with a history of MI. Routine follow-up examinations, comprehensive cardiac imaging and a high clinical alertness are essential for early diagnosis. By providing meticulous post-MI care, healthcare professionals can improve patients outcomes and reduce mortality.